Multi-element Analysis of South African Wines and their Provenance Soils by ICP-MS and their Classification according to Geographical Origin using Multivariate Statistics - van der Linde, G.; Fischer, J.L.; Coetzee, P.P. (South African Journal of Enology and Viticulture, 2016)
Wines and their provenance soils from Robertson, Stellenbosch, Swartland and Walker Bay, four major wineproducing regions in the Western Cape Province of South Africa, were analysed by ICP-MS and the elemental composition was used in multivariate statistical analysis to classify the wines and soils according to geographical origin. In total, 67 wines, 29 white and 38 red, from 22 cellars and their corresponding soils were analysed for 26 elements (in order of mass number): Li, B, Al, Sc, V, Cr, Mn, Co, Ni, Cu, Zn, Rb, Sr, Zr, Nb, Mo, Cd, Sn, Sb, Ba, Ce, Nd, W, Tl, Pb and U in 1:2 diluted wines and microwave-digested soil samples. The elements Li, B, Sc, Mn, Co, Ni, Cu and Rb were identified, using a principle component analysis procedure, as indicators with the ability to discriminate between wines and soils from different geographical origins. A linear discriminant analysis procedure based on the log concentrations of the selected elements was applied to classify 96% of the wines and 100% of the vineyard soils correctly according to point of origin. It was verified that, for the wines and soils from four major wine-producing regions in the Western Cape, a correlation existed between the elemental composition of a wine and that of its provenance soil. This is an important prerequisite for the application of the fingerprinting methodology and a first result of this kind for South African wines.